Jogos digitais no ensino das operações da matemática escolar e a construção de conhecimentos matemáticos - Galo, Charlene Onhas (2024)
The general objective of this research is to analyze the use of digital games in the teaching of mathematics, with regard to the possibility that this resource can contribute to the construction of mathematical knowledge in a 6th-grade class of Elementary School. As theoretical support, studies by authors regarding the use of digital games as a teaching tool were primarily discussed, as well as those that emphasize the use of digital technologies in mathematics education. The research is qualitative in nature and took place during the months of September and October of the 2023 academic year, with students from a 6th-grade class of Elementary School. The research was developed over six meetings, with the first one involving the application of a written diagnostic assessment task, followed by a questionnaire completed by the students to obtain information about the integration and use of digital games in mathematics classes. During the subsequent four meetings, a workshop was held in the school’s computer lab with three digital board games focusing on the four basic mathematical operations. In the final meeting, students participated in a discussion circle as a methodological proposal, promoting dynamic and productive communication about the processes. As a result, the students exhibited a playful relationship with the games, which in turn proved to be effective educational tools in addressing the students’ learning difficulties. It was found that the use of digital games enhanced the construction of mathematical knowledge, dynamizing and bringing playfulness to the process of teaching and learning mathematics for students from a municipal school in Cachoeiro de Itapemirim, located in the southern region of the State of Espírito Santo